11–23% Cr steels for solid oxide fuel cell interconnect applications at 800 °C – How the coating determines oxidation kinetics. (22nd April 2023) - Reddy, M.J.; Chausson, T.E.; Svensson, J.E.; Froitzheim, J.
Abstract: The present work investigates the low-cost steels AISI 441, AISI 430, and AISI 444 against the tailor-made high Cr steel Crofer 22 APU (22.9 wt% Cr) at 800 °C in simulated solid oxide fuel cell (SOFC) cathode conditions. Furthermore, a low Cr steel, AISI 409 (11.4 wt% Cr) is included in the study. The oxidation, chromium evaporation, and area-specific resistance (ASR) of the uncoated and Ce/Co-coated steels are studied for up to 3000 h. Ce/Co-coated steels showed significant improvement in behaviour compared to their uncoated counterparts. The oxidation and chromium evaporation behaviour between the uncoated steels varied substantially while the Ce/Co coated steels exhibited highly similar behaviour. The area-specific resistance of the coated low-cost steels was on par with Crofer 22 APU. However, 430 formed a continuous silica layer, resulting in a higher ASR after 3000 h. Cross-sections of the uncoated and Ce/Co-coated steels were analysed using a scanning electron microscope and energy dispersive X-ray spectroscopy. Graphical abstract: Image 1 Highlights: Uncoated ferritic steels have different chromium evaporation and oxidation rate. The steels show virtually identical, improved behaviour when coated with Ce/Co. The Ce/Co coatings reduced chromium evaporation by 60–100 times to uncoated. Ce/Co-coated AISI 409 (11.4 %Cr) didn't show breakaway corrosion after 3000 h.